Digital ray reconstruction through distraction osteogenesis: A retrospective study of 82 rays with long-term follow-up. Issue 7 (July 2015) - Vekris, Marios; Lykissas, Marios; Pakos, Emilios; Gelalis, Ioannis; Korompilias, Anastasios; Soucacos, Panayotis; Beris, Alexandros
Abstract Purpose The aim of the present study was to present the long-term radiographic results with distraction osteogenesis in traumatic or congenital length discrepancies of long bones of the hand. Methods The medical records and radiographs of 65 consecutive patients (27 metacarpals and 55 phalanges) with either traumatic or congenital digital length discrepancies were retrospectively reviewed. The mean follow-up was 8.2 years. The mean distraction period was 21 days with a distraction rate of 4 × 0.25 mm/day. Callus consolidation was obtained in all patients. Results The bones were lengthened by a mean amount of 17.5 mm, with a mean increase in bone length of 68 ± 17.3%. The mean healing index was 28.57 days/cm. Ray reconstruction with callus distraction can be applied effectively in skeletally immature or mature patients with congenital differences of the hand or amputated fingers. Conclusion A distraction rate of 1 mm/day proved to be a safe rate of lengthening in both metacarpals and phalanges.